Psychiatric Assistance Dog Use for People Living With Mental Health Disorders - Lloyd, Janice; Johnston, Laura; Lewis, Julia (Frontiers in Veterinary Science, 2019)
A psychiatric assistance dog (PAD) is a service dog that is trained to assist its handler (owner) who has been diagnosed with a mental health condition such as post-traumatic stress disorder (PTSD), schizophrenia, depression, anxiety, or bipolar disorder. Literature searches reveal that little is known about the population of people who own PADs, the types of dogs used or the functions they provide. One third (n = 199) of PAD owners in Australia registered with the charity “mindDog” participated in an online survey designed to better understand the person and dog team. Participants learned about PADs through the internet (37%), health care practitioners (32%), or family/friends (30%). The dogs in the sample were of varying age, gender and breed. The most common reasons for people to choose a dog to be a PAD were temperament (60%) and size/weight (48%). Just under half (48%) of the dogs had been acquired by the owner specifically to be trained as a PAD, and the rest were existing pets. All the dogs were trained by the owner or a combination of the owner and a qualified trainer; none were trained exclusively by assistance/service dog provider organizations. The median age of the participants at the time of data collection was 47 years, ranging from 10 to 75 years. Most (77%) identified as female. Depression (84%), anxiety (social 61%; generalized 60%), PTSD (62%), and panic attacks (57%) were the most reported mental health diagnoses. Tasks the dogs performed for their owners included: reduction of anxiety through tactile stimulation (94%); nudging/pawing to bring back to the present (71%); interrupting undesirable behavior (51%); constant body contact (50%); deep pressure stimulation (45%) and blocking contact from other people (42%). PAD usage decreased (46%), increased (30%) or did not change (24%) participants' use of psychiatric or other health care services. Decrease in service use was mainly due to reduced suicide attempts, and less requirement for hospitalization and medication; increased use was mainly due to enhanced ability to attend appointments. Results of this study show that PAD owners have differing mental health diagnoses, and their dogs perform different tasks to support them in daily life. Every participant described the relationship with his/her PAD as positive, suggesting that a successful working partnership does not require the dog to have been bred or raised specifically for the role. A better understanding of this population and the person-dog relationship will inform the appropriate choice, training and use of PADs for people living with mental health problems.